A nationwide cross-sectional study of difficulty waking up for school among adolescents. Issue 11 (22nd June 2021) - Kinoshita, Yu; Itani, Osamu; Otsuka, Yuichiro; Matsumoto, Yuuki; Nakagome, Sachi; Osaki, Yoneatsu; Higuchi, Susumu; Maki, Jike; Kanda, Hideyuki; Kaneita, Yoshitaka
Abstract: Study Objectives: To determine the prevalence of and risk-factors for difficulty waking up for school among adolescents. Methods: We used a self-administered questionnaire (140 junior high schools [JHSs]; 124 senior high schools [SHSs]) selected randomly in 2012 from throughout Japan. Results: Total response rate: 60.7%. Data from 38 494 JHS and 61 556 SHS students were analyzed. The prevalence of at least one instance of school tardiness/absence due to difficulty waking up over a 30-day period was 10.9 (95% confidence-interval:10.5–11.3)%/2.9(2.7–3.1)% for JHS-boys and 7.7(7.3–8.1)%/2.0(1.8–2.2)% for JHS-girls. The prevalence was 15.5(15.1–15.9)%/5.6(5.3–5.9)% for SHS-boys and 14.4(14.0–14.8)%/5.9(5.6–6.2)% for SHS-girls. We used ordinal regression to identify the risk factors associated with the experience of school tardiness/absence. Factors significantly associated with school tardiness in all four groups (JHS boys/girls, SHS boys/girls) were "no-participation-in-club-activities, " "early-morning-awakening, " "feeling bad throughout a morning, " "drinking, " and "smoking." Among associated factors, the highest odds ratio was found for monthly smoking-days (none vs. at least one-day or more) for JHS-girls at 5.30(3.57–7.85). Factors significantly associated with school absence in all four groups were "no wishing to go to university, " "no participation in club activities, " "disorders of initiating and maintaining sleep, " "long internet use, " "drinking, " "smoking, " "poor-mental-health" and "feeling bad throughout a morning." Among associated factors, the highest odds ratio was found for monthly smoking-days (none vs. at least one-day or more) for JHS-girls at 4.60(3.45–6.15). Conclusions: These results suggest that the risk factors for difficulty waking up among adolescents are sleep status, lifestyle, and mental health, which can indicate the presence of an underlying disease.